2017
DOI: 10.1038/icb.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

Restimulation‐induced T‐cell death through NTB‐A/SAP signaling pathway is impaired in tuberculosis patients with depressed immune responses

Abstract: Production of IFN-γ contributes to host defense against Mycobacterium tuberculosis (Mtb) infection. We previously demonstrated that Signaling lymphocytic activation molecule-associated protein (SAP) expression on cells from tuberculosis (TB) patients was inversely correlated with IFN-γ production. Here we first investigated the role of NK, T and B cell antigen (NTB-A)/SAP pathway in the regulation of Th1 response against Mtb. Upon antigen stimulation, NTB-A phosphorylation rapidly increases and afterwards modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(160 reference statements)
1
6
0
Order By: Relevance
“…Work from our group and others has illuminated a central role for SAP/SLAM receptor signaling in governing RICD sensitivity in T cells [10, 11, 13]. Our results further underscore the importance of SAP-driven signaling in this process, demonstrating that Tregs have evolved to disable this signaling pathway via FOXP3-dependent SAP repression to resist RICD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Work from our group and others has illuminated a central role for SAP/SLAM receptor signaling in governing RICD sensitivity in T cells [10, 11, 13]. Our results further underscore the importance of SAP-driven signaling in this process, demonstrating that Tregs have evolved to disable this signaling pathway via FOXP3-dependent SAP repression to resist RICD.…”
Section: Discussionsupporting
confidence: 63%
“…XLP-1 patients harbor null mutations in the signaling adaptor SLAM-associated protein (SAP), which is required for RICD [9, 10]. Indeed, work from our lab and others has shown that SAP associates with the signaling lymphocyte activation molecule (SLAM) family receptor NTB-A to potentiate TCR signal strength by displacing SHP-1 and recruiting LCK instead of FYN, which facilitates downstream signaling for apoptosis after TCR re-engagement [11-13]. SAP also represses DGKα to maintain a sufficient pool of diacylglycerol for robust TCR signaling [7, 14], further highlighting SAP as a central player in promoting RICD of effector T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we showed that immunological attributes matched clinical parameters studied in TB in Argentina (6, 16, 43). Thus, we next decided to analyze whether there was a relationship between clinical parameters commonly studied in tuberculosis and the genetic variants of the rs763780 SNP.…”
Section: Resultsmentioning
confidence: 73%
“…We observed the maximum proportion of patients carrying the C variant in the LR subpopulation, individuals that display the most severe tuberculosis. We have previously reported that HR patients had significantly higher percentages of total lymphocytes and exhibited higher PPD diameters compared to LR patients; and that LR individuals had severe pulmonary lesions and a striking loss of weight compared to HR subjects (6, 16, 43). Surprisingly, by evaluating clinical parameters usually studied in tuberculosis, we did not find significant differences in the radiological pulmonary lesions of the patients carrying the different genotypes of the rs763780 SNP.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation